Electrophysiological asymmetry in vincristine-exposed children with acute lymphoblastic leukemia: Evidence from bilateral nerve conduction studies - Filip Jevic; Ross Andel; Josef Kraus; Alena Kobesova (PLoS ONE, 2026)
Vincristine-induced peripheral neuropathy (VIPN) is a frequent complication of therapy for acute lymphoblastic leukemia (ALL) in children. Beyond acute toxicity, VIPN may affect motor development, balance, and quality of life in survivors. Although often assumed to be symmetric, the extent of electrophysiological asymmetry has not been systematically evaluated. This study aimed to quantify side-to-side differences in vincristine-exposed children using bilateral nerve conduction studies (NCS). Forty-seven bilateral NCS assessments were performed in 47 children with ALL (32 post-treatment survivors and 15 on active therapy). Distal latencies, amplitudes, and conduction velocities were compared between sides using intraclass correlation coefficients (ICC), Cohen’s kappa, and McNemar’s test at three hierarchical levels: individual parameters, nerve-level classifications, and limb-level neuropathy. Motor nerve parameters, particularly compound muscle action potential amplitude and conduction velocity, showed only fair to moderate inter-side agreement (ICC range 0.28–0.64), with the lowest concordance observed in the peroneal and ulnar nerves. In contrast, sensory latencies demonstrated excellent symmetry (ICC > 0.90). Whole-nerve classifications for motor nerves revealed fair to moderate agreement (kappa 0.38–0.49), while NCS-defined polyneuropathy classification showed substantial agreement (kappa = 0.66). Furthermore, marked amplitude asymmetry (side-to-side ratio < 0.5) was observed in 40.4% of peroneal nerves. These results suggest that electrophysiological asymmetry is a frequent feature of pediatric VIPN and may have clinical relevance. Recognition of asymmetry does not fully align with the traditional view of VIPN as a symmetric neuropathy and supports consideration of bilateral NCS in clinical and research settings. Improved awareness of asymmetry may help improve diagnostic accuracy and inform the development of future assessment criteria. Because asymmetry could contribute to postural imbalance, gait deviations, and reduced functional capacity, its detection may be relevant for rehabilitation planning and for guiding future studies on long-term motor outcomes in this pediatric population.